Trasformazioni sociopolitiche a destra. L’evoluzione da Alleanza Nazionale a Fratelli d’Italia: primi risultati di una ricerca empirica - Canzano Giansante, Antonello (SocietàMutamentoPolitica, 2023)
The article examines the evolution of the Italian right framed in the broader phenomenon of the European right. The theoretical framework of reference comforts us in analysing the ideological configuration of the galaxy of the new right, which presents itself in its substantial homogeneity and in the affirmation of a new policy that, founded on the call to the people, claims the demand for an essential modification of the current socio-economic reality and of the prevailing socio-cultural conformation. The Italian Right contains specific peculiarities outlining a path that has led it to abandon legacies, appeals, echoes of the old ideological baggage. The path has not been linear. At first it accelerated in a moderate direction, then it saw a discontinuity in the direction of the recovery of certain radical traits. Our investigation into the right and the path that today sees Fratelli d’Italia as the main political formation of the Italian right is mainly based on research that sees local administrators and the Party on the Ground in general as the object of analysis, which we will use here to infer the main orientations and relevant confirmations on important ideological aspects. All this formed the basis of a broader research project involving much of the local and national ruling class, the conclusions of which will be offered in a subsequent publication. Here, the initial results and the analysis of official documents have been extremely useful in tracing the path taken by the Italian right.